Wood density in forests of Brazil's 'arc of deforestation': Implications for biomass and flux of carbon from land-use change in Amazonia - Nogueira, Euler Melo (Forest Ecology and Management, 2020)
Wood density is an important variable in estimates of forest biomass and greenhouse-gas emissions from land-use change. The mean wood density used in estimates of forest biomass in the Brazilian Amazon has heretofore been based on samples from outside the "arc of deforestation", where most of the carbon flux from land-use change takes place. This paper presents new wood density estimates for the southern and southwest Brazilian Amazon (SSWA) portions of the arc of deforestation, using locally collected species weighted by their volume in large local inventories. Mean wood density was computed for the entire bole, including the bark, and taking into account radial and longitudinal variation. A total of 403 trees were sampled at 6 sites. In the southern Brazilian Amazon (SBA), 225 trees (119 species or morpho-species) were sampled at 4 sites. In eastern Acre state 178 trees (128 species or morpho-species) were sampled at breast height in 2 forest types. Mean basic density in the SBA sites was 0.593 ± 0.113 (mean ± 1 S.D.; n = 225; range 0.265-0.825). For the trees sampled in Acre the mean wood density at breast height was 0.540 ± 0.149 (n = 87) in open bamboo-dominated forest and 0.619 ± 0.149 (n = 91) in dense bamboo-free forest. Mean wood density in the SBA sites was significantly higher than in the bamboo dominated forest but not the dense forest at the Acre site. From commercial wood inventories by the RadamBrasil Project in the SSWA portion of the arc of deforestation, the wood volume and wood density of each species or genus were used to estimate average wood density of all wood volume in each vegetation unit. These units were defined by the intersection of mapped forest types and states. The area of each unit was then used to compute a mean wood density of 0.583 g cm-3 for all wood volume in the SSWA. This is 13.6% lower than the value applied to this region in previous estimates of mean wood density. When combined with the new estimates for the SSWA, this gave an average wood density of 0.642 g cm-3 for all the wood volume in the entire Brazilian Amazon, which is 7% less than a prior estimate of 0.69 g cm-3. These results suggest that current estimates of carbon emissions from land-use change in the Brazilian Amazon are too high. The impact on biomass estimates and carbon emissions is substantial because the downward adjustment is greater in forest types undergoing the most deforestation. For 1990, with 13.8 × 103 km2 of deforestation, emissions for the Brazilian Amazon would be reduced by 23.4-24.4 × 106 Mg CO2-equivalent C/year (for high- and low-trace gas scenarios), or 9.4-9.5% of the gross emission and 10.7% of the net committed emission, both excluding soils. © 2007 Elsevier B.V. All rights reserved.